Agro-industrial fruit co-products in Colombia, their sources and potential uses in processed food industries: a review (2015)
Fruit agribusinesses generate large amounts of byproductswith diverse characteristics that are inherent to the fruitsfrom which they come, which are a source of great use potentialbecause their compositions include molecules that are currentlyof high interest (antioxidants and dietary fiber). It is clear that,without correct handling and disposal, theses fruits present aproblem due to the environmental pollution that large quantitiesof residues can generate. Although there are varied uses for agroindustrialco-products, this review focused on the potential usesthat co-products could have in different processed food matrices.In this sense, this paper led to the revelation that one of theprincipal objectives of the reviewed research was to conditionco-products for use in processed foods in an attempt to takeadvantage of the bio-active compounds they contain, principallythe natural antioxidant activity, which especially enjoys acceptanceby consumers of processed foods.